Suggerimenti di lettura - Macario, Giorgio; di Mattia, Francesca; Jedlowski, Paolo; Pedrotti, Alessandro; Nardini, Marisa; Scanarotti, Roberto; Lazzarini, Carmine; Favaro, Graziella; Capellino, Marilena; Bandini, Gianfranco; et al. (Autobiografie. Ricerche, pratiche, esperienze, 2025)